Effective School Management - Everard, K. B.; Morris, Geoff; Wilson, Ian (London : SAGE Publications, Limited Thousand Oaks : SAGE Publications, Incorporated [Distributor], 2004)
`This edition is more focussed on the leadership demands of managers both within the school and its community. This book can be used as a source of reference for anyone on a school manager position, written by people who practice management on educational organizations themselves, it deals with the fundamentals of what management is the many roles of the manager' - Headteacher Update `The book is clearly structured, with an informative table to contents. Each chapter ends with practical tasks which could be sued either by an individual at home or by groups in a training session. The book is worth adding to any staffroom library for the section of "time-management techniques" alone. If only I has acquired the habit of "starting each day by writing list of all the things that should be done that day and starring them to indicate importance" in recognition that "the critical distinction is between what is urgent and what is important"!' - Education Review `This book provides a thoroughly comprehensive guide to managing staff, meetings, motivating people, managing conflict, health and safety and much more' - Nursery Equipment This popular book has been thoroughly updated for its Fourth Edition . Targeting the contents directly to the needs of today's school manager. The book is now even more directed towards the leadership demands on managers, both within the school and in its community setting. New sections have been written to deal with emerging pressures on heads: - the increasing complexity of employment legislation - the management of risk - performance management - flexibility in the curriculum - the inclusion agenda - team development and leadership - the effect of the government's new approach to early years education. Recent research and developments have been incorporated and the content has been extensively updated. The authors' fresh and readable style, coupled with their use of proven interactive exercises, makes the book a first choice for busy heads and senior staff in all schools.
Previous ed.: 1996.
Includes bibliographical references and index.
Scholarly & Professional
BIED
Complimentary copy from BIED
Keywords: School Management and Organization; School management and organization -- Great Britain; Educational planning -- Great Britain; Social science